Methodology of the study of the characterology of delinquent behavior - Trush, Vladimir Mihailovich; Gomonov, Nikolai Dmitrievich; Timohov, Viktor Petrovich (Юридические исследования, 2024)
In the framework of this article, the authors state the expediency of further searching for determinants of delinquent behavior at the junction of criminology and criminal psychology. Therefore, by clarifying and developing methodological tools, it is expected to significantly supplement knowledge about the mechanisms of committing crimes. The object of the study is the social relations formed in the process of the study of the characterology of delinquent behavior. The subject of the study is the characteristics of persons demonstrating offending behavior, criminal law, scientific papers reflecting the problems analyzed in the work. The research base was made up of convicts in special regime colonies, law-abiding citizens, as well as a set of scientific works on criminology and legal psychology by domestic and foreign authors. The purpose of this work is defined as the identification of the basic foundations, theoretical and methodological foundations of the characterology of delinquent behavior. The methodological basis of the work consists of the laws and categories of dialectical materialism and a historical approach to the interpretation of socio-legal phenomena. The methodology is represented by a complex of general scientific and private scientific methods. The main methods of work are extrapolation and the method of expert assessments. The novelty of the study lies in the proposals made to clarify the methodology used in the study of the characterology of individuals, which determines various variants of delinquent, including criminal, behavior. As a result of the conducted research, the authors conclude that further refinement of the methodological apparatus makes it possible to identify the essence of the mechanism of committing a crime. In addition, the presented basic principles can be used as the basis for studying the deviant manifestations of an individual, based on a phenomenological approach – consideration of the features of speech activity. Further specification of research tools will make it possible to more clearly identify the qualitative and quantitative characteristics of criminogenic infection of a person. This information will provide an opportunity to improve the quality and effectiveness of individual crime prevention. At the end of the work, the prospect of scientific research in this area was announced.